Social Interaction in the Library: A Student Psychological Perspective - Afrina Cut; Suud Fitriah M.; Yanti Nurrahma; S Safrinal (SHS Web of Conferences)
Social interactions in the library are important for students’ academic experience and psychological well-being. academic expertise and students’ psychological well-being. Libraries support academic collaboration and provide a safe social space, reducing isolation and increasing social connectedness. However, these interactions can also be social pressures. Understanding students’ psychological perspectives on social interactions in the library helps institutions design spaces and programs that support their academic and psychological needs. That supports their academic and psychological needs. The purpose of this study is to explore the role of social interaction in the library in students’ academic experience and psychological well-being. This research aims to understand how libraries support academic collaboration, reduce isolation, and increase social connectedness, and identify ways to design spaces and programs that meet students’ academic and psychological needs. The purpose of this study is to explore the role of social interaction in the library in students’ academic experience and psychological well-being. This research aims to understand how libraries support academic collaboration, reduce isolation, and increase social connectedness, and identify ways to design spaces and programs that meet students’ academic and psychological needs. This research uses the literature review method by reviewing articles from Google Scholar from 2019-2023. Articles included were in English and Indonesian, focused on libraries, and available in full text. Data were analysed narratively to identify psychological factors that influence social interactions in libraries, evaluate their impact on students’ psychological well-being, and identify best practices in library design and management. The results showed three main trends: the importance of social environments in libraries to support interaction and learning, the integration of information and communication technology (ICT) such as augmented reality (AR) to enhance social interaction, and the impact of social media and gadget use on social interaction. Libraries that support social interaction can improve students’ academic engagement and well-being. Future research includes longitudinal mixed-methods studies, diversification of data collection methods, and exploration of technology integration and external factors that influence student engagement.